Pengembangan Model Bimbingan Klasikal Berbasis Panca Jiwa Pondok bagi Konselor Pesantren - Djovana, Amalya El Fatihah; Purwoko, Budi; Nursalim, Mochamad (Jurusan Bimbingan dan Konseling Islam, 2026)
The digital era requires Islamic boarding schools (pesantren) to strengthen character education while responding to technological advancements and the evolving needs of students. This study aimed to develop a Panca Jiwa Pondok-based Classical Guidance Model as a practical guide for Islamic boarding school counselors to internalize the core values of sincerity (ikhlas), simplicity, independence, Islamic brotherhood (ukhuwah diniyah), and togetherness among students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, document analysis, validation questionnaires, and pretest–posttest assessments. Product validation involved two subject-matter experts, one media expert, and five Islamic boarding school counselors as prospective users. Product trials were conducted through a small-group trial involving 10 students and a large-group trial involving 40 students. The validation results indicated feasibility scores of 62% and 76% from the subject-matter experts, 92% from the media expert, and 77% from the prospective users after revisions were made based on the validators' recommendations. The implementation results demonstrated an increase in the students' average understanding of the Panca Jiwa Pondok values across all assessed aspects after participating in the classical guidance program. The final product of this study is a Panca Jiwa Pondok-based Classical Guidance Model accompanied by a practical implementation guide for Islamic boarding school counselors. The developed model was found to be feasible for use as a guideline in implementing classical guidance services to strengthen character education in Islamic boarding schools.